1989
DOI: 10.1901/jaba.1989.22-315
|View full text |Cite
|
Sign up to set email alerts
|

Self‐recording of Attention Versus Productivity

Abstract: We investigated the relative effects of self-recording of attentive behavior and self-recording of academic productivity with 5 upper elementary-aged special education students in their special education dassroom. Following baseline, both self-recording treatments were introduced according to a multielement design. After the multielement phase, we assessed the pupils' performance under a choice condition, faded the overt aspects of the treatment program according to a withdrawal design, and probed maintenance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
40
1
3

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 15 publications
1
40
1
3
Order By: Relevance
“…All studies reported increased on-task behavior for both selfmonitoring approaches; neither form of self-monitoring emerged as dearly superior. Lloyd et al (1989), Rooney et al (1985), and Roberts and Nelson (1981) Leary, 1979).The present study compared the effects of selfmonitoring attention, academic productivity, and academic accuracy on mathematics performance. Content difficulty was controlled by having students self-monitor problems they performed accurately but for which they required practice to become fluent (responding correctly and quickly).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…All studies reported increased on-task behavior for both selfmonitoring approaches; neither form of self-monitoring emerged as dearly superior. Lloyd et al (1989), Rooney et al (1985), and Roberts and Nelson (1981) Leary, 1979).The present study compared the effects of selfmonitoring attention, academic productivity, and academic accuracy on mathematics performance. Content difficulty was controlled by having students self-monitor problems they performed accurately but for which they required practice to become fluent (responding correctly and quickly).…”
mentioning
confidence: 96%
“…Numerous studies have shown that self-monitoring either attention or academic responding increases on-task behavior (e.g., Blick & Test, 1987;DiGangi, Maag, & Rutherford, 1991;Hallahan, Lloyd, Kosiewicz, Kauffman, & Graves, 1979;Harris, 1986). However, it remains undear which of the variables in self-monitoring best promotes academic gains (Hallahan & Sapona, 1983;Harris, 1986;Lloyd & Landrum, 1990;Snider, 1987).Advocates of self-monitoring attention stress its simple and practical nature (Lentz, 1988 that any differential effects between the two variables are too small to influence academic achievement (Hallahan & Sapona, 1983;Lloyd, Bateman, Landrum, & Hallahan, 1989;Lloyd & Landrum, 1990). Proponents of self-monitoring academic outcome, on the other hand, question the link between on-task behavior and achievement and cite research indicating that targeting productivity or accuracy is more likely to affect academic responding (e.g., Hoge & Andrews, 1987;Klein, 1979;Petersen & Swing, 1982;Ruggles & LeBlanc, 1985;Treiber & Lahey, 1983).…”
mentioning
confidence: 99%
See 3 more Smart Citations